Pengaruh Penyuluhan GERMAS Menggunakan Media Video terhadap Pengetahuan dan Sikap Kader GERMAS - Rio Herwanto; Nila Susanti; Harlyanti Muthma'innah Mashar (Politeknik Negeri Jember, 2022)
The increase in PTM cases encourages the government and the community to immediately take action. The government has made various efforts to overcome this by encouraging people to have a healthy lifestyle, one of which is through GERMAS. This study aims to examine the effect of counseling on the knowledge and attitudes of cadres in GERMAS in the working area of ​​the Kuala Pembuang I Health Center. This research is a quasi-experimental study with a one-group pretest-posttest design. The population in this study were all active cadres in the working area of ​​the Kuala Pembuang I Health Center. The selection of the subjects of this study was the entire population selected by purposive sampling so the number of subjects was 18 people. Data obtained through the process of interviewing and filling out a questionnaire then analyzed using a paired t-test. The statistical analysis results showed that there were differences in cadres’ knowledge before and after the GERMAS counseling using video media (p = 0.000). Meanwhile, the difference in the attitude of cadres about GERMAS before and after giving counseling using video media was obtained p-value = 0.000 (p <0.05). This results has shown that there are differences in the attitudes of cadres about GERMAS before and after being given counseling with video media. This research has concluded that providing counseling with video media can increase the knowledge and attitudes of cadres in GERMAS. There is a need for a programmatic extension of the cooperation between the public health center and the local health office to create a healthy and clean environment.